Monitoring of iot-based Wind and Solar Hybrid Power Plants for Agricultural Irrigation Systems - Prasetiyo, Budhi; Widyaningsih, Wiwik Purwati; H, Yusuf Dewantoro; Suwarti, Suwarti (Politeknik Negeri Semarang, 2022)
The use of renewable energy, one of which is Hybrid Power Plants (PLTH). The PLTH used in this study is a wind and solar power plant. To keep the plant from being damaged and prevent a decrease in tool performance, PLTH was developed based on the Internet of Things (IoT). IoT will later monitor the performance of the plant. In this study using the ESP32 TTGO SIM800L microcontroller, the sensors used were DC voltage sensors, current sensors (ACS712), wind speed sensors (anemometers), wind direction sensors (wind vanes), and water flow sensors. The research began with designing the relationship between components, working on monitoring and programming systems on software, installing outdoor sensors and installing monitoring systems, and ending with data observations. The results obtained on the observation of data, the best error percentage values are presented by various sensors with values less than 6%.